Physical and mechanical evaluation of dental resin composite after modification with two different types of Montmorillonite nanoclay. (September 2021) - Elmergawy, Fagr Hassan; Nassif, Mohammed Salah; El-Borady, Ola M.; Mabrouk, Mostafa; El-Korashy, Dalia I.
Highlights: Montmorillonite can be successfully synthesized and organo-modified with PMMA. Incorporation of Montmorillonite in resin composite didn't affect DC up to 1 wt%. 0.5 wt% of PMMA/MMT enhanced composite flexure strength compared to the control. PMMA/MMT increased the micro-hardness of composite in all tested concentrations. Composite showed no perceptible color differences when adding0.5 wt% of nanoclay. Abstarct: Objectives: Evaluation of degree of conversion (DC), flexural properties, micro-hardness and color change (ΔE00 ) of dental resin composite after modification with two types of organo-modified Montmorillonite (MMT) nanoclay; an experimentally synthesized polymethyl-methacrylate modified MMT nanoclay (PMMA/MMT), and a commercially available one (Cloisite20A). Methods: MMT was synthesized by sol-gel technique, organo-modified with polymethyl-methacrylate and characterized using EDX, XRD and FTIR. PMMA/MMT and Cloisite20A nanoclay were added to flowable resin composite in 0.5, 1 and 1.5 wt% concentrations. Unmodified resin composite was used as control group. DC was assessed by FTIR, flexural properties were tested by three-point bending test using a universal testing machine, micro-hardness was analyzed by Vickers micro-hardness tester and color change (ΔE00 ) was evaluated using a reflective spectrophotometer. SEM and elemental mapping assessment were performed to evaluate nanoclay distribution in resin composite. Data were analyzed using One-way ANOVA followed by Tukey's post hoc test, in addition to Two-way ANOVA ( p ≤ 0.05). Weibull analysis was used to analyze flexural strength results. Results: Characterization results revealed successful preparation of PMMA/MMT. DC results showed insignificant difference up to 1 wt% of nanoclay concentration. Addition of 0.5 wt% of PMMA/MMT significantly increased flexural properties, while addition of 1.5 wt% of PMMA/MMT significantly decreased flexural properties. Micro-hardness results revealed a significant increase in PMMA/MMT groups in all tested concentrations. ΔE00 results showed that color change was clinically acceptable on adding 0.5 wt% nanoclay. Conclusion: PMMA/MMT in 0.5 wt% is a promising nanofiller for resin composite that significantly enhanced flexural strength and micro-hardness without compromising DC and color.